2019
DOI: 10.2196/10794
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Based Predictors of Mindfulness Meditation Mobile App Usage: A Survey and Cohort Study

Abstract: Background Mindfulness meditation has become increasingly popular over the last few years, due in part to the increase in mobile apps incorporating the practice. Although studies have demonstrated the potential of mindfulness meditation to positively impact health, little has been uncovered about what predicts engagement in mindfulness meditation. Understanding the predictors of mindfulness meditation may help practitioners and phone app developers improve intervention strategies and app experienc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Mobile mental health apps have the potential to reach millions of individuals who are unable to access individualized face-to-face or video therapy services [ 19 , 20 ]. There are many mobile mental health apps currently available, but while research is emerging on how apps work in optimal, highly supported conditions [ 12 , 21 , 22 , 26 , 27 ], less is known about how apps are used by the general population without additional input from providers. For example, what is the most efficacious dosage and duration of use, and how are people inclined to use the app without specific guidance?…”
Section: Introductionmentioning
confidence: 99%
“…Mobile mental health apps have the potential to reach millions of individuals who are unable to access individualized face-to-face or video therapy services [ 19 , 20 ]. There are many mobile mental health apps currently available, but while research is emerging on how apps work in optimal, highly supported conditions [ 12 , 21 , 22 , 26 , 27 ], less is known about how apps are used by the general population without additional input from providers. For example, what is the most efficacious dosage and duration of use, and how are people inclined to use the app without specific guidance?…”
Section: Introductionmentioning
confidence: 99%
“…The initial search yielded 822 hits, with 698 after the removal of duplicates ( Figure 1 ). After title and abstract review, 41 full-text articles were assessed for eligibility, and 33 studies met the inclusion criteria and were retained in the final review [ 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The majority of the studies utilized a noncontrolled timeseries or pre-post design, with follow-up periods ranging from 1 week to 6 months ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the majority of the articles demonstrated support for impulsivity as a moderator, three studies assessed the moderating role of impulsivity in the intention–behavior gap but found no statistical significance [ 33 , 34 , 35 ]. Specifically, Chevance and colleagues’ [ 33 ] investigation of physical activity, Crandall’s [ 34 ] assessment of mindfulness mobile app usage, and Stevens’ [ 35 ] evaluation of alcohol consumption did not demonstrate a significant association.…”
Section: Resultsmentioning
confidence: 99%
“…Data from a randomized waitlist-controlled trial and a prospective cohort study of Headspace have demonstrated good overall efficacy for improving outcomes such as quality of life and anxiety in women diagnosed with breast cancer [21,23]. However, the overall science of app-based MBIs is still in its early stages and far from achieving consensus about efficacy of intervention platforms, as well as understanding mechanisms of action [12,17]. For example, this is demonstrated by a randomized trial of Headspace with college students that reported no effects for the mindfulness component of Headspace's app-based program [24].…”
Section: Benefits Of App-based and Online Mindfulness Interventionsmentioning
confidence: 99%
“…Most research studies of this nature have tested MBIs such as MBCR when delivered face to face in a group-based setting, although a variety of online-based and digitally adapted MBIs are now available to patients through smartphone apps [11]. Mobile app-based MBIs for cancer patients and survivors allow for considerable flexibility and appeal, especially since they eliminate the need for travel time and problems due to scheduling conflicts [11,12].…”
Section: Introductionmentioning
confidence: 99%